International opportunity recognition by South African entrepreneurial firms - Willard, Candice (My University, 2016)
The global market is a dynamic, competitive environment offering business growth and development, and as such a pull towards international activities exists for firms. Despite this globalisation of markets, international entrepreneurship research has not focussed on the opportunity recognition process in an international context. In addition, the cross-national differences that may exist, and the validation of perspectives to emerging economies, is poorly understood. This research was conducted in South Africa, a country considered to be an emerging economy, with the purpose of ascertaining how local entrepreneurial firms recognise international opportunities, and the main factors influencing this process. This was done using a quantitative statistical research methodology, in the form of a cross-sectional study. An online self-administered survey was utilised for data collection, which was then subjected to the research selection criteria. Prior experiential knowledge and the levels of entrepreneurial orientation, in terms of proactiveness, risk-taking and innovativeness, did not seem to have a significant effect on the international recognition process by South African firms. The effect of organisational learning could not be conclusively drawn. However, international social networks, in relation to the amount of time invested in interacting with contacts, and developing and maintaining contacts, seemed to have a significant effect on this process. This research provides the initial insights into an under-researched area, and contributes to international entrepreneurship research with empirical testing of a sample from South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management specialising in Entrepreneurship and New Venture Creation Johannesburg, 2015
Keywords: International business enterprises; Entrepreneurship--South Africa